Signifikansi: Proses Pencarian Makna Terhadap Teks-teks Agama (Menyibak Pemikiran Nasr Hamid Abu Zaid) - Muzakki, Akhmad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2004)
Naturally, said Gadamer, word belongs to and is taken from reality. Human being looks for appropriate words as form of expression for reality. Ontologically, language created by human being is not only as a means of communication and thinking, but rather it is seen as the manifestation of reality, while they are articulating that language. Therefore, the meaning of a word is in the concept of thought. In the linguisticÂ theory of Saussure, a word is a sign related to signifiant (which gives meaning) and signifie (which is given meaning). The signifiant gives form or expression while signifie concept or meaning. The relationship between the signifiant and the signifie based on the social convention is called signification, or